2021
DOI: 10.3390/curroncol28010034
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic Stressors and Psychological Symptoms in Breast Cancer Patients

Abstract: Background. The current Coronavirus disease 2019 (COVID-19) pandemic is a highly stressful event that may lead to significant psychological symptoms, particularly in cancer patients who are at a greater risk of contracting viruses. This study examined the frequency of stressors experienced in relation to the ongoing coronavirus pandemic and its relationship with psychological symptoms (i.e., anxiety, depression, insomnia, fear of cancer recurrence) in breast cancer patients. Methods. Thirty-six women diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 24 publications
4
85
3
1
Order By: Relevance
“…Results indicated that about a quarter of this sample experienced clinically elevated FCP, as defined by the most recent psychometric evidence ( Fardell et al, 2017 ). A recent study of non-metastatic breast cancer survivors during the COVID-19 pandemic found that 53% had FCP scores in the clinical range ( Massicotte et al, 2021 ), but used a lower cutoff score recommended in earlier work ( Simard and Savard, 2009 ). Using this same lower cutoff, 60% of the current sample had clinical levels of FCP, yielding findings consistent with those reported by Massicotte et al (2021) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Results indicated that about a quarter of this sample experienced clinically elevated FCP, as defined by the most recent psychometric evidence ( Fardell et al, 2017 ). A recent study of non-metastatic breast cancer survivors during the COVID-19 pandemic found that 53% had FCP scores in the clinical range ( Massicotte et al, 2021 ), but used a lower cutoff score recommended in earlier work ( Simard and Savard, 2009 ). Using this same lower cutoff, 60% of the current sample had clinical levels of FCP, yielding findings consistent with those reported by Massicotte et al (2021) .…”
Section: Discussionmentioning
confidence: 99%
“…The current recommended cutoff score to establish clinical levels on the FCRI-SF is a sum score > 22 ( Fardell et al, 2017 ), equivalent to a mean score > 2.44, which we used here as an approximate indicator of FCP severity on our adapted measure. To facilitate comparison to other recently published findings on FCP during the COVID-19 pandemic ( Massicotte et al, 2021 ), we also reported the percentage of scores exceeding the lower cutoff of > 13 (equivalent to a mean score > 1.44), which is often still used as recommended by original measure developers ( Simard and Savard, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Romito et al (2020) from Italy, reported 36% patients of lymphoma with anxiety, 31% with depression and 36% with post-traumatic stress disorder (PTSD), as analyzed through Hospital Anxiety and Depression Scale (HADS-A) and (HADS-D). Increased anxiety, insomnia and depression in breast cancer patients was observed using the HADS, Insomnia Severity Index, Generalized Anxiety Disorder Questionnaire (GAD-7) and Impact of Events Scale Revised (IES-R) (Juanjuan et al, 2020;Massicotte et al, 2021). Another study from China, including 834 patients with breast cancer, showed a prevalence of depression, anxiety and insomnia in 21.6, 15.5 and 14.7% of the cohort, respectively.…”
Section: Introductionmentioning
confidence: 99%